Recent progress on sodium ion batteries: Potential high-performance anodes - Li, L.; Zheng, Y.; Zhang, S.; Yang, J.; Shao, Zongping; Guo, Z. (Royal Society of Chemistry, 2018)
Due to massively growing demand arising from energy storage systems, sodium ion batteries (SIBs) have been recognized as the most attractive alternative to the current commercialized lithium ion batteries (LIBs) owing to the wide availability and accessibility of sodium. Unfortunately, the low energy density, inferior power density and poor cycle life are still the main issues for SIBs in the current drive to push the entire technology forward to meet the benchmark requirements for commercialization. Over the past few years, tremendous efforts have been devoted to improving the performance of SIBs, in terms of higher energy density and longer cycling lifespans, by optimizing the electrode structure or the electrolyte composition. In particular, among the established anode systems, those materials, such as metals/alloys, phosphorus/phosphides, and metal oxides/sulfides/selenides, that typically deliver high theoretical sodium-storage capacities have received growing interest and achieved significant progress. Although some review articles on electrodes for SIBs have been published already, many new reports on these anode materials are constantly emerging, with more promising electrochemical performance achieved via novel structural design, surface modification, electrochemical performance testing techniques, etc. So, we herein summarize the most recent developments on these high-performance anode materials for SIBs in this review. Furthermore, the different reaction mechanisms, the challenges associated with these materials, and effective approaches to enhance performance are discussed. The prospects for future high-energy anodes in SIBs are also discussed.